Variations on a Theme: Antennal Lobe Architecture across Coleoptera. - Martin Kollmann; Rovenna Schmidt; Carsten M Heuer; Joachim Schachtner (PLoS ONE, 2016)
Beetles comprise about 400,000 described species, nearly one third of all known animal species. The enormous success of the order Coleoptera is reflected by a rich diversity of lifestyles, behaviors, morphological, and physiological adaptions. All these evolutionary adaptions that have been driven by a variety of parameters over the last about 300 million years, make the Coleoptera an ideal field to study the evolution of the brain on the interface between the basic bauplan of the insect brain and the adaptions that occurred. In the current study we concentrated on the paired antennal lobes (AL), the part of the brain that is typically responsible for the first processing of olfactory information collected from olfactory sensilla on antenna and mouthparts. We analyzed 63 beetle species from 22 different families and thus provide an extensive comparison of principal neuroarchitecture of the AL. On the examined anatomical level, we found a broad diversity including AL containing a wide range of glomeruli numbers reaching from 50 to 150 glomeruli and several species with numerous small glomeruli, resembling the microglomerular design described in acridid grasshoppers and diving beetles, and substructures within the glomeruli that have to date only been described for the small hive beetle, Aethina tumida. A first comparison of the various anatomical features of the AL with available descriptions of lifestyle and behaviors did so far not reveal useful correlations. In summary, the current study provides a solid basis for further studies to unravel mechanisms that are basic to evolutionary adaptions of the insect olfactory system.